The effect of regulatory requirements and esg promotion on market liquidity - Péter Csóka; Judit Hevér (Magyar Nemzeti Bank, 2023)
Liquidity and market risk are key considerations in financial markets, especially in times of financial crises. For this reason, regulatory attention to and measures in these fields have been on the rise for the past years. Based on practical experience, regulations aiming at ensuring funding liquidity or, in general, reducing certain risky positions have the side effect of reducing market liquidity. To understand this effect, we extend a standard general equilibrium model with transaction costs of trading, endogenous market liquidity, and the modeling of regulation. We prove that higher regulatory requirements or divesting bad ESG assets reduces market liquidity.
Keywords: G11; 330; Market liquidity; Market risk; Liquidity risk; General equilibrium model; Regulatory requirement; ESG related assets